Adverse maternal, fetal, and newborn outcomes among pregnant women with SARS-CoV-2 infection: an individual participant data meta-analysis - Smith, ER; Oakley, E; Grandner, GW; Ferguson, K; Farooq, F; Afshar, Y; Ahlberg, M; Ahmadzia, H; Akelo, V; Aldrovandi, G; Tippett Barr, BA; Bevilacqua, E; et al. (BMJ Publishing Group, 2023)
Introduction Despite a growing body of research on the risks of SARS-CoV-2 infection during pregnancy, there is continued controversy given heterogeneity in the quality and design of published studies.